2020
DOI: 10.5194/acp-20-13753-2020
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the trend in the occurrences of the “warm Arctic–cold Eurasian continent” temperature pattern

Abstract: Abstract. The recent increasing trend of “warm Arctic, cold continents” has attracted much attention, but it remains debatable as to what forces are behind this phenomenon. Here, we revisited surface temperature variability over the Arctic and the Eurasian continent by applying the self-organizing-map (SOM) technique to gridded daily surface temperature data. Nearly 40 % of the surface temperature trends are explained by the nine SOM patterns that depict the switch to the current warm Arctic–cold Eurasia patte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The interannual WACE pattern has often been explained by the planetary wave train induced by anomalous heating over Gulf Stream 30 or the Arctic sea ice loss 5 8 . Likewise, the CAWE or the negative WACE pattern has been explained by the stationary wave initiated over the North Atlantic 10 , 31 , 32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The interannual WACE pattern has often been explained by the planetary wave train induced by anomalous heating over Gulf Stream 30 or the Arctic sea ice loss 5 8 . Likewise, the CAWE or the negative WACE pattern has been explained by the stationary wave initiated over the North Atlantic 10 , 31 , 32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an increasing occurrence of the so-called warm Arcticcold continents pattern in winter (Overland et al, 2011). Whether the pattern is due to sea ice loss and amplified warming in the Arctic (Cohen et al, 2013;Overland et al, 2021), SST-driven teleconnections from the North Pacific and North Atlantic (Yu et al, 2020), or inherent variability of the climate system (Blackport and Screen, 2020), in any case the pattern has partly compensated for the greenhouse warming over northern continental mid-latitudes in winter. Comparing the two halves of our study period, the November-March warming at the 850 hPa level (based on ERA5) has two prominent spatial patterns: (1) the Arctic has warmed faster than Europe, and (2) eastern Europe has warmed faster than western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The SOM has been increasingly used to distinguish the weather patterns of atmospheric circulation (Johnson, 2013; Bao and Wallace, 2015; Yu et al ., 2020; Yu et al ., 2021). In this study, the SOM training and analysis are based on daily spatial anomalies of T2M during early winter (defined as Dec 1–Jan 31) of the years 1979–2021.…”
Section: Methodsmentioning
confidence: 99%